High Resolution Mapping of the Indica-Derived Rice Blast Resistance Genes II. Pi-ta2 and Pi-ta and a Consideration of Their Origin - Krystyna Rybka; Masaru Miyamoto; Ikuo Ando; Akira Saito; Shinji Kawasaki (Molecular Plant-Microbe Interactions, 1997)
The indica-derived rice blast resistance genes Pi-ta2 and Pi-ta, introgressed into a japonica background, were mapped on the middle of chromosome 12 with restriction fragment length polymorphism (RFLP)/random amplified polymorphic DNA (RAPD) markers and several nearly isogenic lines (NILs). Pi-ta2 cosegregated with XNpb 289 and 196, and was flanked by closely linked markers at 0.3 (ta2-1) and 0.7 cM (XNpb 088, 319/079) on the left (up) side, and at 0.3 (RUBss) and 0.7 cM (XNpb316) on the right (down) side of the map, in F2 analyses of Pi No. 4 × japonica crosses, with 160 recessive homozygotic individuals corresponding to 320 chromosomes. CHEF (contour-clamped hexagonal electric field) Southern blotting suggested that XNpb088 and XNpb239-1, both very close to Pi-ta2, were spanned by a 170-kb band, suggesting about 500 to 750 kb/cM as the physical/genetic distances ratio in the crosses of Pi No. 4 × japonica, which was rather low in recombination ratio, in this region. Pi-ta was mapped to the position overlapping Pi-ta2 by graphical genotype analysis of an NIL with a very narrow introgressed region, Shimokita. This result suggested that these functionally related genes are allelic or at least very closely located, and that they may be derived from a common ancestral gene. However, RFLP analyses of the NILs of these two genes indicated that they are derived from rather different genomes, refuting the report that NILs of Pi-ta share a common donor with those of Pi-ta2. This indicates that the two genes differentiated at a rather ancient time. Two other pedigrees, describing spontaneous recent origins of Pi-ta in japonica, were also refuted and a single indica origin of the gene was indicated.